Effect of Fermentation on Some Chemical and Nutritive Properties of Berlandier Nettle Spurge (Jatropha cathartica) and Physic Nut (Jatropha curcas) Seeds - Peace, Oladele Ebun- Oluwa; Aladesanmi A., Oshodi (Pakistan Journal of Nutrition, 2008)
The seeds of Jatropha curcas and Jatropha carthatica were subjected to traditional fermentation (a common way of producing local condiments in Nigeria) with the aim of improving the nutritional properties. The result of the study revealed that the raw seeds have high nutrient level (protein, carbohydrate, fat, crude fibre and minerals) and moderate anti-nutrient level. Fermentation increased the antinutrient content of the seeds as well as most of the minerals. Acid values for the oil of the fermented seeds were higher while unsaponifiables were appreciably reduced by fermentation.